PENGARUH KONSERVATISME AKUNTANSI DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE (Studi Kasus Pada Perusahaan Indeks LQ45 Periode 2015-2021) - Indah Febriandini; Ilham Illahi (CV. Adiba Aisha Amira, 2023)
This research aims to find out and analyze how much influence accounting conservatism and audit committees have on tax avoidance. The population in this research is the LQ45 Index companies listed on the Indonesia Stock Exchange (BEI) in 2015-2021, namely 22 companies, using a purposive sampling method. The data used is secondary data obtained from the Indonesian Stock Exchange (BEI) via the Idx website. In this research, 2 independent variables are used, namely Accounting Conservatism and Audit Committee, while the dependent variable is Tax Avoidance. The method used in this research uses Descriptive Statistical Tests, Classical Assumption Tests, multiple regression analysis, determinant coefficient tests and hypothesis tests. The research results prove that the first hypothesis of accounting conservatism has no effect on tax avoidance as evidenced by a large significant value of 0.05, namely 0.721 > 0.05. The second hypothesis shows that the audit committee has a negative effect on tax avoidance as evidenced by a small significant value of 0.05, namely 0.043 < 0.05 and seen from the t value which is negative, the audit committee has a negative effect on tax avoidance. The third hypothesis shows that accounting conservatism and the audit committee together have a significant effect on tax avoidance as evidenced by a significant value of 0.023 < 0.05. The results of the R2 determinant coefficient test show an R square value of 0.712 or 71.2%, this means that the independent variables, namely accounting conservatism and the audit committee, have an influence of 71.2% on the dependent variable, namely tax avoidance, while 28.8% is influenced by other variables.